2007
DOI: 10.1002/ijc.22561
|View full text |Cite
|
Sign up to set email alerts
|

Genes and molecular pathways related to radioresistance of oral squamous cell carcinoma cells

Abstract: To identify genes associated with radioresistant oral squamous cell carcinoma (OSCC), we compared gene expression signatures between OSCC cell lines exhibiting radioresistance and cells with radiosensitivity after X-ray irradiation in a dose-dependent manner using Affymetrix GeneChip analysis with Human Genome-U133 plus 2.0 GeneChip. The microarray data identified 167 genes that were significantly overexpressed in radioresistant cells after X-ray irradiation. Among the genes identified, 40 were mapped to 3 hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 45 publications
2
56
0
Order By: Relevance
“…We recently developed the strategy of using a knowledge-based network approach to search for candidate genes relevant to the treatment of oral cancers (Kasamatsu et al, 2005;Higo et al, 2006;Ishigami et al, 2007). Thus, this study aimed to explore further the global changes in Ca 2 þ -binding protein genes associated with OSCCs by applying network development tools to expand on microarray analysis methods.…”
mentioning
confidence: 99%
“…We recently developed the strategy of using a knowledge-based network approach to search for candidate genes relevant to the treatment of oral cancers (Kasamatsu et al, 2005;Higo et al, 2006;Ishigami et al, 2007). Thus, this study aimed to explore further the global changes in Ca 2 þ -binding protein genes associated with OSCCs by applying network development tools to expand on microarray analysis methods.…”
mentioning
confidence: 99%
“…These findings strongly suggested the oncogenic properties of the FGFR3-mutated receptor. FGFR3, an elevated mRNA expression level of which was detected in radioresistant human SCC cell lines in our previous study (Ishigami et al, 2007), was found to be a candidate for radioresistant enhancements in SCC cells using microarray analysis. A more recent study also reported a relationship between FGFR3 and radiation sensitivity in artificially FGFR3-reduced oral SCC cells …”
Section: Fgfr3 Inhibition For Radioresponse Enhancement In Scc Cellsmentioning
confidence: 79%
“…Although previous studies have reported an association between enhanced radiosensitivity in oral SCC and certain gene expression (Shintani et al, 2003;Ishigami et al, 2007), to the best of our knowledge, the current report is the first on the use of the combination of an FGFR3 inhibitor and radiation in vitro and in vivo. Finally, the current data supported the idea that combination therapy with radiation and an FGFR3 inhibitor increases the therapeutic efficacy of radiation in human cancers including SCCs.…”
Section: Fgfr3 Inhibition For Radioresponse Enhancement In Scc Cellsmentioning
confidence: 80%
See 2 more Smart Citations